Tropeirismo e criatórios de mulas em Lagoa Vermelha, nordeste do RS (1914-1955) - Silva, Itací de Souza e (2011)
The tropeirismo of mules in Brazil had its beginning in the first decades of century XVIII when they had been iscovered mineral precious in the center of the country, more necessarily in the region of Minas Gerais. The transport of the gold, silver and diamonds was made for muares (donkeys and mules) searched in the South of Brazil. The Rio Grande do Sul becames the main supplier of products of animal origin and muares the central region, through the fair of Sorocaba. For return of the decade of 1860 the commerce of muares entered in decline, being that in the Rio Grande do Sul the tropeirismo with mules continued having its economic importance, serving as alternative for the load transport. Red lagoon, whose foundation occurred in reason of the tropeira activity, commercialized muares bred in the region products cultivated in the city with the areas of German and Italian settling. On the other hand it bought of the colonies basic products that were necessary to the subsistence of the farms. The rupture of this system if made to feel since 1950 when alternative investments in the region as in the cattle bovine, the agricultural culture, and the substitution of the animal transport for the automobile had appeared. This boarding reveals, therefore excellent,therefore it reconstitutes to peculiar aspects of the tropeirismo of mules in the city, occurrence enters the years of 1914 the 1955, making possible, thus, to understand also the historical roots of its formation. This inquiry was based on verbal sources, registers and bibliographical on the subject, having been made a research in the region of Red Lagoon next to criatórios of mules, old creators, tropeiros, carreteiros, in historical archives, etc. the research points, at last, that Red Lagoon had a great dynamism in this process, having had an intense linking with the Italian and German colonial region of the state gaucho as well as the incentive in the creation of muares in the city